The role of military cooperatives in supporting Indonesia’s defense economy through improving soldiers’ welfare - Lucky Agusta; Sri Sundari (Institute of Accounting Research and Novation (IARN), 2025)
Military cooperatives have a strategic role in supporting a country's defense economy by improving the welfare of soldiers. The welfare of soldiers as one of the components in the Minimum Essential Force (MEF) is important in addition to other components such as Main Equipment of Weaponry Systems; Base Facilities and Training Areas; Defense Industry; and Organization and Budget. This paper analyzes how military cooperatives can be an effective economic instrument in creating welfare for military members. This research uses a qualitative-descriptive approach through Biddle and Thomas' (1966) role theory approach that focuses on role conflict and role ambiguity. The research was conducted by collecting secondary data from relevant literature, including journals, books, and official documents. The results of the analysis show that military cooperatives can improve the welfare of soldiers through increased income, education and ownership of assets such as residential houses, reduce dependence on third parties, and encourage efficiency in the management of military logistics needs. This has implications for strengthening the economy and national stability, which can be achieved through improving the welfare of soldiers, providing a multiplier effect for the community's economy, and reducing the burden on the state budget to maintain a stronger national defense. The role of military cooperatives must continue to be developed as an alternative solution to the problem of limited state budget towards the fulfillment of MEF in the framework of a strong national defense. This paper concludes that strengthening military cooperatives can contribute to the stability of the national defense economy.